2022
DOI: 10.1002/aps3.11492
|View full text |Cite
|
Sign up to set email alerts
|

Seed dormancy and germination of the endangered exceptional Hawaiian lobelioid Brighamia rockii

Abstract: Premise The Campanulaceae (Lobelioideae) is the Hawaiian plant family with the most endangered and extinct species. Although seeds of Hawaiian lobelioids are desiccation tolerant, the species are exceptional (i.e., they present challenges at various stages of the conventional ex situ conservation chain) due to their generally poor seed survival at the conventional seed‐banking temperature (–18°C). Both morphological dormancy (MD) and morphophysiological dormancy (MPD) have been identified in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Similar to other Campanulaceae families, the seeds of the native Korean C . takesimana species had underdeveloped embryos from their parent plants at the time of dispersal and showed MD that required embryo development before germination [ 13 , 14 ]. Before radicle protrusion, the E:S ratio increased from 0.40 to 0.67, and the cumulative germination did not reach 36.00% within 30 d in the temperature regime groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to other Campanulaceae families, the seeds of the native Korean C . takesimana species had underdeveloped embryos from their parent plants at the time of dispersal and showed MD that required embryo development before germination [ 13 , 14 ]. Before radicle protrusion, the E:S ratio increased from 0.40 to 0.67, and the cumulative germination did not reach 36.00% within 30 d in the temperature regime groups.…”
Section: Discussionmentioning
confidence: 99%
“…From the perspective of forest restoration, it is necessary to not only understand the ecology of wild plants but also understand the propagation method of seeds with high genetic diversity for restoration [ 13 ]. Thus, regardless of seed source, species-specific knowledge of dormancy-release and germination requirements is needed for the successful cultivation of plants from seeds for application in different industries [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For many species, exceptional or not, seed germination requirements are poorly understood or unknown. Wolkis et al ( 2022 ) address this issue with the exceptional species Brighamia rockii H. St. John by investigating dormancy and germination requirements. Using a systematic approach to uncovering germination requirements not only informs best practices for the conservation of the species but allows researchers to make inferences on the longevity of seed viability in both the seed bank and the wild.…”
Section: Identification Of Exceptional Species Using Seed Biologymentioning
confidence: 99%
“…For this reason, the species is classified as exceptional under exceptionality factor 3 (EF3; Pence et al, 2022 ). A recent seed dormancy and germination study of the only other species in the genus, B. rockii H. St. John, found that seeds are able to germinate in darkness, suggesting the species is unlikely to form a long‐lived soil seed bank (Wolkis et al, 2022 ). If we assume B. insignis seeds behave similarly, these findings further support the notion that reintroductions will be needed to reestablish extirpated populations.…”
mentioning
confidence: 99%